Chloroplast phylogenomics in Camelina (Brassicaceae) reveals multiple origins of polyploid species and the maternal lineage of C. sativa - Brock, Jordan R; Mandáková, Terezie; McKain, Michael; Lysak, Martin A; Olsen, Kenneth M (Horticulture research, 2022)
The genus Camelina (Brassicaceae) comprises 7-8 diploid, tetraploid, and hexaploid species. Of particular agricultural interest is the biofuel crop, C. sativa (gold-of-pleasure or false flax), an allohexaploid domesticated from the widespread weed, C. microcarpa. Recent cytogenetics and genomics work has uncovered the identity of the parental diploid species involved in ancient polyploidization events in Camelina. However, little is known about the maternal subgenome ancestry of contemporary polyploid species. To determine the diploid maternal contributors of polyploid Camelina lineages, we sequenced and assembled 84 Camelina chloroplast genomes for phylogenetic analysis. Divergence time estimation was used to infer the timing of polyploidization events. Chromosome counts were also determined for 82 individuals to assess ploidy and cytotypic variation. Chloroplast genomes showed minimal divergence across the genus, with no observed gene-loss or structural variation. Phylogenetic analyses revealed C. hispida as a maternal diploid parent to the allotetraploid Camelina rumelica, and C. neglecta as the closest extant diploid contributor to the allohexaploids C. microcarpa and C. sativa. The tetraploid C. rumelica appears to have evolved through multiple independent hybridization events. Divergence times for polyploid lineages closely related to C. sativa were all inferred to be very recent, at only ~65 thousand years ago. Chromosome counts confirm that there are two distinct cytotypes within C. microcarpa (2n = 38 and 2n = 40). Based on these findings and other recent research, we propose a model of Camelina subgenome relationships representing our current understanding of the hybridization and polyploidization history of this recently-diverged genus.